Dog and mouse: toward a balanced view of the mammalian olfactory system - Barrios, Arthur W.; Sánchez-Quinteiro, Pablo; Salazar, Ignacio (Frontiers in Neuroanatomy, 2014)
Although the most intensively studied mammalian olfactory system is that of the mouse, in which olfactory chemical cues of one kind or another are detected in four different nasal areas (the main olfactory epithelium, the septal organ, Grüneberg’s ganglion, and the sensory epithelium of the vomeronasal organ), the extraordinarily sensitive olfactory system of the dog is also an important model that is increasingly used, for example in genomic studies of species evolution. Here we describe the topography and extent of the main olfactory and vomeronasal sensory epithelia of the dog, and we report finding no structures equivalent to the Grüneberg ganglion and septal organ of the mouse. Since we examined adults, newborns and foetuses we conclude that these latter structures are absent in dogs, possibly as the result of regression or involution.The absence of a vomeronasal component based on VR2 receptors suggests that the vomeronasal organ may be undergoing a similar involutionary process.